Effects of different distillation patterns on main compounds of Chinese Luzhou‐flavour raw liquors. Issue 3 (21st April 2017) - Ding, Xiaofei; Huang, Jun; Wu, Chongde; Zhou, Rongqing
Abstract : This study aimed to investigate the effects of different distillation patterns on main compounds of Chinese Luzhou ‐flavour liquor. Results showed that more volatiles of raw liquor might originate from fresh grains for a newly constructed pit. A modest ( p  = 0.05) increase in the total amount of volatiles was found in the heart liquor from fermented grains added to fresh grains and rice hulls to distillate (AG pattern), reaching a maximum value of 1012.22 mg/L. The percentage of esters in the AG pattern ranged from 81.22 to >95.03% compared with samples from fermented grains only added to rice hulls to distillate (NG pattern). Acids in the heart liquor obtained by the AG pattern were higher than those for NG, but the corresponding proportion was opposite. Alcohols were detected at ~1.62% in NG pattern but were 1.42% in AG. Cyanide and ethyl carbamate content in the head liquor were far higher than those in the heart and tail liquor. In particular, cyanide content dramatically increased after adding fresh grains during the distillation process. Copyright © 2017 The Institute of Brewing & Distilling